Marriage and misgeneration in colonial societies - (:unkn) unknown (My University, 2015)
The conquest of large colonial empires by European powers, followed by migratory flows, more or less important depending on places and periods, gave birth to new societies. The most important human groups, indigenous, European born settlers and their descendants, and sometimes slaves snatched from the African continent, mixed, more or less early, more or less intensely. Unions, legally registered or not, and misgeneration lead to the appearance of mixed-blood generations and to a process of creolisation. The numerical strength of these human groups, and the existence of barriers between them, produced various degrees of misgeneration that the authorities of the colonial societies tried to identify and to classify. The sixteen texts gathered in this book study the way that these populations got mixed, and the place of mixed-blood people in the new societies. These issues are tackled in a long-term perspective, about various territories, from Canada to Bolivia, from the French West Indies to Madagascar, from Algeria to Angola
Keywords: African Research